Learning to plan and planning to learn: resolving the planning school/learning school debate - Brews, Peter J.; Hunt, Michelle R. (Strategic Management Journal, 1999)
This paper resolves the long-standing debate between the two dominant process schools in strategy. Analysis of the planning practices of 656 firms shows that formal planning and incrementalism both form part of ‘good’ strategic planning, especially in unstable environments. Environment neither moderates the need for formal planning nor the direction of the planning/performance relationship, but does moderate firm planning capabilities and planning flexibility. In unstable environments planning capabilities are far better developed and formal plans more amenable to change. The planning/performance relationship is, however, moderated by planning duration: at least four years of formal planning are required before external performance associations are noted. Copyright © 1999 John Wiley & Sons, Ltd.